1971
DOI: 10.1044/jshr.1402.323
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Aid Distortion and Consonant Identification

Abstract: An experiment was conducted with 34 normal-hearing listeners to determine the effects of distortion (generated by a single hearing aid) on consonant identification in noise. Five experimental conditions were employed in which measured harmonic distortion ranged from approximately 1% (high fidelity) to 35%. Each listening condition involved playback of recorded test material at a constant sensation level. Results showed that average consonant identification scores, relative to the high-fidelity condition, decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The reason is uncertain. Perhaps excessive hearing-aid compression alone or combined with residual cochlear compression at high intensities (65–80 dB SPL) generated excessive distortion that degraded the temporal representation of speech (recall that RECE HI was a contributor to component PC6: temporal processing deficits) and hindered intelligibility ( Bode & Kasten, 1971 ; Boothroyd, Springer, Smith, & Schulman, 1988 ; Marriage, Moore, Stone, & Baer, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason is uncertain. Perhaps excessive hearing-aid compression alone or combined with residual cochlear compression at high intensities (65–80 dB SPL) generated excessive distortion that degraded the temporal representation of speech (recall that RECE HI was a contributor to component PC6: temporal processing deficits) and hindered intelligibility ( Bode & Kasten, 1971 ; Boothroyd, Springer, Smith, & Schulman, 1988 ; Marriage, Moore, Stone, & Baer, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…The REIG 50dB and REIG 65dB were included as predictors because they can affect audibility and reduced audibility decreases speech-in-noise intelligibility (e.g., Peters et al., 1998 ). The RECE LO and RECE HI were included as predictors because compression might distort the amplified speech presented to the hearing-aid user and distortion can reduce speech intelligibility ( Bode & Kasten, 1971 ). A second reason was that RECE LO and RECE HI may interact with residual cochlear compression (BMCE) or cochlear amplification loss, and the interaction may influence speech intelligibility.…”
Section: Appendix A: Detailed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The author also stated that most types of noise, especially those with intense lowfrequency components, have a severely detrimental effect on intelligibility. Bode and Kasten (1971), studying 34 normalhearing listeners under conditions of varying distortion, showed that consonant identification decreased by 15% to 29% as distortion levels increased. The introduction of moderate levels of distortion alone did not significantly decrease intelligibility.…”
Section: The Effect Of Distortion On Speech Intelligibilitymentioning
confidence: 97%